Pembuatan modul fisika berbasis pendekatan sets pada materi pemanasan global dengan konsep zerowaste lifestyle (pola hidup minim sampah) untuk peserta didik SMA/MA kelas XI - Dian Indah Aulia; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2020)
The purpose of this study to develop a Physics Module based on the approval of "science, environmental technology, and society" (SETS) which expected to improve students attitudes, skills, and students perspectives to understanding in environmental management. This type of research is "Research & Development" (R&D) using Plomp model. The validity assessment of the modules was obtained from 3 Physics lecturers at the Faculty of Mathematics and Natural Sciences UNP as experts, as well as the practicality value of one to one and small groups obtained from students of class XI SMA Pertiwi 1 Padang. The instrument collects data using validity test sheets and practicality tests. The data analysis technique used is descriptive statistical analysis.Based on the analysis of research data, the results obtained from the Physics Module based on Obtaining SETS with the concept of lifestyle zerowaste have an average value of 91.52 with a very strong category of validity. Then, in terms of the use of the Physics Module it has an average practicality value for one 77.19 with a quite practical category. Whereas the mean value obtained in the Assessing components of small group practicality is 81.87. So, it can be concluded that the SETS-based Physics Module with the zerowaste lifestyle concept of global material is valid, and practically used as a source of independent learning for high school students in class XI.